UNITED STATES CIVIL AVIATION BOARD (CAB) SMOKING RULEMAKING - SCHAFFER,D (Tufts Archival Research Center, 2007)
Report discussing the government agencies responsible for regulating smoking aboard aircrafts: the Federal Aviation Administration (FAA) and the Civil Aeronautics Board (CAB). Presents the history behind smoking rulemaking, focusing on the institution of separate sections aboard aircrafts for smokers and non-smokers. Discusses Jimmy Carter's Airline Deregulation Act and its relationship to airplane smoking policy. Affirms the widespread public support of the rule to separate smokers and non-smokers. Describes additional smoking restrictions the CAB is considering.